THE INFLUENCE OF OPERATIONAL FACTORS ON EMPLOYEE TRUST AND COMMITMENT AND ITS IMPACT ON SME BUSINESS PERFORMANCE - Antonio, Ferdi; Theresia, Sherly (Master of Management, Faculty of Economics and Business, Diponegoro University, 2023)
This study aims to investigate how operational factors in SMEs, influence employee trust and commitment and impact business performance using empirical data. The operational factors that were examined namely group formality, internal communication, teamwork, skill, knowledge sharing, and IT support. The eligible 208 respondents who have been working in the SME for more than a year, were obtained through a questionnaire and analyzed using the PLS-SEM method. The empirical findings demonstrate that the six operational influences significantly employee commitment and trust (p<0,05), except for group formality and teamwork skills to trust. Interestingly, commitment shows a larger impact on SMEs' business performance compared to trust, likewise, commitment could mediate the impact of trust. In addition, the model with the total sample shows moderate prediction accuracy (R2: 0,508). Furthermore, the FIMIX PLS identified the data heterogeneity and provide a segment analysis that provides a higher predictive capability (R2: 0,936) to ascertain the explanatory and predictive capability of the model. Finally, the outcomes enable SMS business leaders to make pertinent observations in the organization and encourage the effort to gain employee commitment.